1960
DOI: 10.1080/00288233.1960.10419865
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shearing time on wool

Abstract: Monthly measurements have been made of wool, grease, and suint production, and fibre diameter and length, in pre-and post-Iamb-shorn Romney ewes over a period of 18 months. The growth of wool is some three times faster in summer than in late winter-early spring and the minimum rate decreases and occurs later with increasing number of lambs. Pre-Iamb-shorn wool is sound because it is shorn near the time when fibre diameter is at a minimum, and wool shorn at any other time has a thin region where it is likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1960
1960
2000
2000

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Coop, 1953;Wildman, 1957), environmental temperature (e.g. Ferguson et al 1949 andWodzicka, 1960) and even time of shearing (quoted by Story & Ross, 1960). The present data do not provide a basis for discrimination between these hypotheses as the conditions of short day length, low temperatures and short rations are inextricably bound up in the natural environment of the hill sheep and it was felt that the first essential was a study of the between and within sheep variation in wool production and fleece structure under the influence of the total environmental pattern.…”
Section: Discussion (A) Seasonal Changes In Fleece Components Of In-lmentioning
confidence: 98%
See 1 more Smart Citation
“…Coop, 1953;Wildman, 1957), environmental temperature (e.g. Ferguson et al 1949 andWodzicka, 1960) and even time of shearing (quoted by Story & Ross, 1960). The present data do not provide a basis for discrimination between these hypotheses as the conditions of short day length, low temperatures and short rations are inextricably bound up in the natural environment of the hill sheep and it was felt that the first essential was a study of the between and within sheep variation in wool production and fleece structure under the influence of the total environmental pattern.…”
Section: Discussion (A) Seasonal Changes In Fleece Components Of In-lmentioning
confidence: 98%
“…Suggestions that the procedure of clipping would itself cause differences in subsequent growth rate have been investigated by Story &Ross (1960) andWodzicka (1960). In both cases, the results suggested that the cumulative growth rate was greater than that of continuously growing samples but in neither case were the results significant.…”
Section: (C) Effect Of Clipping On Subsequent Growthmentioning
confidence: 99%
“…Jones et al (1944) and Doney (1958), using range Rambouillets and Merinos respectively, reported increases of 15-20 %. An experiment described by Coop (1953) and limited information from Story & Ross (1960) and Doney & Smith (1961) all suggested similar differences in Corriedale, Romney and Scottish Blackface sheep, respectively. In the first series of the present report, non-pregnant ewes on hill grazing produced about 20% more greasy wool than ewes rearing single lambs on the same grazings.…”
Section: Total Fleece Weightmentioning
confidence: 96%
“…Trials have been carried out over a number of seasons of the effect on the wool production of Romney and Corriedale ewes, of shearing either before or after lambing (Story and Ross 1959). The staple strength was measured of one staple from the side of each ewe in the 1955 and 1956 seasons.…”
Section: Discussion Of the Results Of Some Staple-strength Testsmentioning
confidence: 99%
“…for the Corriedale samples. The mean values for the staple strength (maximum loads) of each group of ewes have been reported by Story and Ross (1959). A more comprehensive picture of these results is given in Table 3, where data on work, extension at maximum load and at staple break, as well as the weight of the staples tested and the variation of the various measurements in the groups are given.…”
Section: Discussion Of the Results Of Some Staple-strength Testsmentioning
confidence: 99%